THE IMPACT OF PERSONAL INNOVATIVENESS ON THE BEHAVIORAL INTENTION TO USING TOURISM MOBILE APPLICATIONS OF GENERATION Z IN HO CHI MINH CITY, VIETNAM - Nguyen Thi Bich DAO; Do Nguyen Tuan ANH (Geo Journal of Tourism and Geosites)
The advancement of technology has significantly transformed various activities in human life, including tourism. Mobile technology, especially mobile applications, has become an integral part of users’ travel experiences. Generation Z, with their natural and proficient access to technology, has become one of the primary user groups of mobile applications in the tourism industry. Recognizing the lack of research on the intention to use mobile applications in tourism, particularly of Generation Z in Vietnam, a generation expected to reshape the tourism industry in the future, this study aims to investigate how personal innovativeness influences the intention to use mobile applications in tourism among Generation Z and mediation of attitudes. To test the proposed hypotheses, the study conducted an online survey using Google Forms targeting Generation Z individuals living and working in Ho Chi Minh City, Vietnam. A total of 318 participants took part in the survey. The collected data were analyzed using the Partial Least Squares Structural Equation Modeling (PLS-SEM) method. Based on the research findings, the study proposed potential solutions for mobile application development businesses, destination management organizations, tourism businesses to enhance the intention to use mobile applications in tourism among Generation Z in Ho Chi Minh City and Vietnam as a whole.